The sayings and conditions of the dying Sufi, in the mirror of the stories of Tazkīrat al-Awlīyā Attar and Nafaḥāt ul-Uns Jami - Sajedeh Nikkhah; Seyed Hasan Tabatabaei (ادبیات عرفانی)
Death is a mystery that mankind has confronted since the dawn of life, and the exploration of this phenomenon has yet to yield definitive answers. Different groups within society hold varying attitudes towards death shaped by their beliefs, thoughts, environments, and lifestyles. Consequently, their approaches to facing death differ significantly. In this article, we aim to analyze the collection of sayings and experiences of Sufis during the final moments of their lives, as presented in the books of Tazkīrat al-Awlīyā by Attar and Nafaḥāt ul-Uns by Jami. In this research, we focus solely on natural death, because mystics believe in voluntary death in addition to natural death, and they believe that such death is possible only by overcoming carnal emotions. Based on this belief, they claim to experience voluntary death prior to physical death, reaching a state of voluntary departure before the natural death that occurs to all human beings. In this study, conducted using a descriptive and analytical method, we collected the last sayings of mystics, which include prayers, expressions of forgiveness, bequests to those around them, and reflections on their feelings and states. Our findings indicate that, in many cases, Sufis, while facing death and experiencing the process of natural dying, expressed similar sentiments and encountered comparable situations. Despite these similarities, noticeable differences can also be observed in their words and experiences during these critical moments. These variations primarily stem from the distinct Sufi philosophies, practices, and psychological factors that influence their perspectives on death.